Microbial Diversity in Mining–Affected Forest Ecosystems: Exploring the Roles of Seasonality and Environmental Factors in Qinyuan County, Shanxi Province - Aijing Yin; Yuan Yuan; Yujin Cui; Xinna Zhang (Diversity)
China has significant mineral resources, but prolonged extraction has caused considerable environmental degradation. Interactions among rhizosphere, phyllosphere, and soil microorganisms, along with host plants, are essential for supporting plant growth and increasing stress tolerance. This study employed high–throughput sequencing to assess microbial diversity and community structure related to four common tree species in the mountainous areas of Shanxi Province, with samples collected from three regions over two seasons and three locations. The dominant fungal and bacterial phyla identified were Ascomycota, Basidiomycota, Mortierellomycota, Pseudomonadota, Actinobacteriota, Gemmatimonadota, Acidobacteria, Myxococcota, and Firmicutes. Alpha–diversity analysis revealed that Taiyue Mountain exhibited the highest fungal diversity among the plots, while Liushenyu displayed the highest bacterial diversity. Alpha–diversity was greater in spring than in summer across the seasons. Significant differences in Alpha–diversity were observed among different tree species, with Betula platyphylla showing the lowest diversity. In comparison to phyllosphere microorganisms, rhizosphere and soil microorganisms exhibited higher diversity, richness, and evenness. Beta–diversity analysis indicated significant differences in fungal and bacterial community composition between spring and summer samples, as well as among samples from leaves, roots, and soil. The assessment of soil physicochemical properties and redundancy analysis demonstrated that soil moisture content and organic matter were key factors influencing the composition of fungal and bacterial communities. These findings provide valuable insights into the structural changes in plant microbial communities in mining areas and the restoration of damaged ecosystems.